2002
DOI: 10.1007/s10162-002-2052-8
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Development of NR2A and NR2B mRNA Expression in Rat Auditory Cortex and Thalamus

Abstract: Sensory cortex in the rat undergoes rapid postnatal development, especially following the onset of sensory function during so-called``critical periods.'' To investigate potential mechanisms in the auditory forebrain involving different NMDA receptor subunits, we have used in situ hybridization to determine expression patterns of NR2A and NR2B mRNA at postnatal days 4, 10, 13, 18, 25, and adult. In auditory cortex, NR2A mRNA expression is initially weak but increases rapidly over 2 weeks. NR2B mRNA levels are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…1, has an r 2 of .026, almost no effect). In pooled analysis there was no main effect nor interaction of age, test, or surgical result in ANCOVA with age group (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), and 20-53) and test (HINT-C and HINT versus PSI and SPIN) as main effects and the change in PTA as a covariate. In summary, results with noise toward the non-atretic ear show that all patients are able to understand signals presented to their new ear when that ear is protected by head-shadow from noise toward their opposite (normal ear).…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…1, has an r 2 of .026, almost no effect). In pooled analysis there was no main effect nor interaction of age, test, or surgical result in ANCOVA with age group (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), and 20-53) and test (HINT-C and HINT versus PSI and SPIN) as main effects and the change in PTA as a covariate. In summary, results with noise toward the non-atretic ear show that all patients are able to understand signals presented to their new ear when that ear is protected by head-shadow from noise toward their opposite (normal ear).…”
Section: Resultsmentioning
confidence: 75%
“…With advancing age the ability to learn or to adapt to change becomes limited [7]. Critical periods occur in the development of human language [8,9], in bird calls [10,11], in gene expression [12], in adaptation to cochlear implants [13][14][15], and in responses to various forms of early trauma or deprivation [16][17][18][19] such as hearing impairment [20,21]. We typically expect monotonic (steadily decreasing) trends in plasticity, especially in bilateral sensory integration after early unilateral visual or auditory deprivation [22,23].…”
mentioning
confidence: 99%
“…In one study, investigating human hippocampus, NR1, NR2A and NR2B levels did not appear to be significantly different between adolescents (n=9) and young adults (n=6) (Law et al, 2003). In another study, in Sprague-Dawley rats, little differences in expression of these subunits were seen between P25 and “adult” rats (Hsieh et al, 2002). Additionally, it has been reported that no effects of age were seen in NR1 and NR2A subunit mRNA between 3, 10 and 30 month old mice (Magnusson et al, 2006).…”
Section: Discussionmentioning
confidence: 94%
“…A number of studies have shown that NMDAR subunit expression is differentially regulated during development (Watanabe et al, 1992, 1993; Monyer et al, 1994; Zhong et al, 1995; Jin et al, 1997; Wenzel et al, 1997; Hsieh et al, 2002; Magnusson et al, 2002; Law et al, 2003; Chang et al, 2009). Most of these studies have demonstrated in the rat that NR2A expression is generally low at birth but then increases up to about P21–P28, whereas NR2B is high at birth and then peaks around P10–21.…”
Section: Discussionmentioning
confidence: 99%
“…At this age, the rat is approaching sexual maturity, and A1 has matured far beyond the normal closure of the critical period window (a month after the birth) (Zhang et al, 2001;Hsieh et al, 2002;Insanally et al, 2009) for passive sound exposure-driven plasticity. Since tone-specific enlargement in A1 representation resulting from transient exposure to sound stimuli is one basic index of critical period plasticity (Zhang et al, 2001), we directly confirmed the postcritical period status of normal rats at this age by exposing them to pulsed 7 kHz tone pips over a week (Fig.…”
Section: Resultsmentioning
confidence: 99%